Peran Kebudayaan Dalam Menguatkan Kerukunan Antar Umat Beragama di Sidamanik, Kabupaten Simalungun - Tifani,, Tamara Dilla; Muktarruddin, Muktarruddin; Ar Rahma, Maulida; Patikasari, Cindy; Guru Singa, Maratus Soleha (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Sidamanik is one of the areas in the Simalungun Regency, North Sumatra province. This Sidamanik area is located between two cultures, namely Islam and Christianity. The livelihood system in Sidamanik is farming, such as cultivating gardens with rice, corn, coffee. Sidamanik also has a business place which is the result of a tea garden. Sidamanik has a very wide tea garden stretching along the road. This place is also a destination for tourists. In terms of inter-religious harmony, the Sidamanik area is also not far behind in other regions. They are still strong in culture and customs in certain matters from their respective beliefs and beliefs. Keywords: The Role of Culture, interreligious harmony